Batu Badang / Afiq Farid Mohamed Azzahar - Mohamed Azzahar, Afiq Farid (Universiti Teknologi MARA, Kedah, 2025)
lnspideo, a renowned animation studio celebrated for its innovation and storytelling prowess, presents on enthralling tole of courage and destiny. Ahmad's journey begins when he stumbles upon a mysterious crystal in on isolated alley, activating a powerful aura that captures the attention of Serigolo Hitom, a monstrous humanoid cursed with a wolf-like form . Desperate to harness the crystal's energy to break his curse and achieve ultimate strength, Serigolo Hitom wields a chilling ability to drain life force and control darkness. To counter this looming danger, Ahmad is mentored by Nenek Keboyon, who grants him a magical belt that allows him to transform into Bodong, the legendary strongman from Malaysian folklore. Entrusted with safeguarding the crystal, Ahmad must confront not only Serigolo Hitom but also his menacing army of beastly followers, as the fate of the world teeters on the brink of chaos. This project, developed by lnspidea, brings Ahmad's story to life with stunning visuals and compelling storytelling. Throughout his mission, Ahmad is forced to grapple with the immense power of Serigala Hitam while embracing the weight of his newfound abilities. The narrative delves into themes of bravery, self-sacrifice, and the enduring resilience of the human spirit against overwhelming darkness. Badang's thrilling confrontations with Serigala Hitam's monstrous minions are both a demonstration of his legendary might and a reflection of Ahmad's internal journey to fulfill his destiny. This enthralling tale seamlessly weaves elements of Malaysian folklore with intense action and profound moral dilemmas, culminating in a climactic showdown that tests Ahmad's courage and strength to their limits. With the world's survival at stake, Ahmad must rise as a true hero to preserve the crystal's extraordinary power.